The literary text as tool of construction a grammatical competence in an EFL class - SLITANE , Kamel (Journal of Social Sciences and Humanities, 2023)
Our research is centered on the teaching of the literary text with a view to building grammar skills, this research is a part of the field of didactics of the literary text and aims to create an atmosphere of motivation in the process of the teaching / learning of French as foreign language and facilitate the activation of knowledge and to put the student in authentic situations.